The Effect of Current Ratio, Return on Assets, Total Asset Turnover and Sales Growth on Capital Structure in Manufacturing Company - Purba, Mohd. Nawi; Sinurat, Erika Kristiany Br; Djailani, Ahmad; Farera, Winda (International Journal of Social Science and Business, 2020)
This study aimed to determine how much effect the Current Ratio, Return on Assets, Total Asset Turnover and Sales Growth have on the Capital Structure of manufacturing companies listed on the IDX from 2016 to 2018. The research method used was descriptive method and multiple linear analysis method. The population of this study was 144 companies with a sample of these companies, namely 73. The data used were financial reports published by the Indonesia Stock Exchange through the website www.idx.co.id. The variables related to this research are the Current Ratio, Return on Assets, Total Asset Turnover, and Sales Growth. The results showed that partially Current Ratio has a negative and significant effect on Capital Structure, Return on Asset did not have a significant effect on Capital Structure, and Total Asset Turn Over has no significant effect on Capital Structure, and Sales Growth has no significant effect on Capital Structure in manufacturing companies listed on the Indonesia Stock Exchange. Simultaneously Current Ratio, Return on Asset, Total Asset Turn Over and Sales Growth together have a significant effect on the capital structure of companies listed on the Indonesia Stock Exchange.